Exploring the factors of learning organization in school education: the role of leadership styles, personal commitment, and organizational culture - Jacqueline Kareem; Harold Andrew Patrick; Nepoleon Prabakaran (Central European Management Journal)
Purpose – This study aims to test the conceptual model of the factors of learning organization and explore the degree of mediation of organizational culture in the relationship between leadership styles, personal commitment, and learning organization in school education. Design/methodology/approach – The learning organization profile (LOP) and OCTAPACE profile served to measure learning organization and organizational culture, respectively. The researchers developed scales to measure principals’ leadership styles and teachers’ personal commitment. Data included 750 school teachers. Findings – This study found a good fit in the proposed conceptual model. The organizational culture had a significant mediating effect on the path of leadership styles and learning organization and a significant mediating effect on the path of personal commitment and learning organization. Originality/value – To promote a more comprehensive learning culture, school principals should consider two specific organizational mechanisms: the intangible cultural components (such as corporate values, beliefs, and norms) and the tangible structural components (such as organizational structure and workflow systems). These two domains play a crucial role in creating a conducive learning environment.